“Fake or not, I’m sharing it”: teen perception about disinformation in social networks - Zozaya Durazo, L.D.; Sádaba, Charo; Feijoo, Beatriz (Young Consumers, 2023)
Purpose: Disinformation has become a latent risk for online audiences, specifically for minors who are commonly exposed to a wide variety of online content at a time they are developing cognitively and emotionally. This paper aims to offer insight on minors’ perception and the tools used by this age group to verify the content to which they are exposed while online. Design/methodology/approach: Twelve focus groups were held in Spain between April and June 2021 with a total of 62 participants aged 11–17. Besides age, sex and socioeconomic group were variables taken into consideration to select the participants. A script covering the intended questions was used to structure the discussion. Findings: Result analysis reveals that minors are excessively confident in their ability to identify false news and feel the need to share content with their online community as a means of participation in discussions or trending topics. Although WhatsApp family groups are seen as a source of misleading news, the study reveals that the family and traditional media (mainly television) act as sources of verification of fake news for minors. In general, minors opt for actions that require less initiative to contrast the content they consume on the internet. Originality/value: This study produces new findings by further deepening the results of the first quantitative study on the relationship between minors and disinformation in Spain using qualitative method from conducting virtual focus groups.
Keywords: critical thinking; disinformation; fake news; hoaxes; minors; social networks; Scopus; Emerging